2005
DOI: 10.1002/pbc.20476
|View full text |Cite
|
Sign up to set email alerts
|

Severe malignancy‐associated hypercalcemia in dysgerminoma

Abstract: Hypercalcemia is a rare complication of pediatric malignant germ cell tumors. The problem may be missed because of unawareness among pediatric oncologists. We describe a 16-year-old girl with an ovarian dysgerminoma associated with severe hypercalcemia, a metabolic abnormality infrequently reported with this disease. We review some of the potential causes of malignancy-associated hypercalcemia and current treatment strategies. It is our recommendation that calcium levels should be monitored in all children wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…Since the patient described here was pregnant and had no phenotypical signs that would suggest relevant syndromic data, she was not asked about, or assessed for, this possibility. An association between dysgerminoma and malignant hypercalcemia 10,18,19 has been described by some authors, but in this case tests showed that the patient was within normal limits. Another peculiarity that attracts attention is the association with dysgerminoma described in some varieties of animals 20,21 .…”
Section: Imaging In Medicine Introductionmentioning
confidence: 57%
“…Since the patient described here was pregnant and had no phenotypical signs that would suggest relevant syndromic data, she was not asked about, or assessed for, this possibility. An association between dysgerminoma and malignant hypercalcemia 10,18,19 has been described by some authors, but in this case tests showed that the patient was within normal limits. Another peculiarity that attracts attention is the association with dysgerminoma described in some varieties of animals 20,21 .…”
Section: Imaging In Medicine Introductionmentioning
confidence: 57%
“…In this case, however, the need to control serum calcium and deal with the acute renal failure prompted careful reconsideration of leading with chemotherapy. First, there was concern that chemotherapy might be ineffective given reports suggesting tumour excision can be necessary (and rarely still not sufficient) for hypercalcaemia control [2,12]. Second, and perhaps most importantly, the anti-tumour effects of chemotherapy and its side effects are non-trivial in the context of a child in hypercalcaemic renal failure.…”
Section: Discussionmentioning
confidence: 97%
“…Previous reports have described removal of isolated ovarian dysgerminomas to control malignant hypercalcaemia in children [2,3]. Rare cases of hypercalcaemia in adults with metastatic dysgerminoma have been managed in a variety ways, ranging from abdominal radiotherapy or chemotherapy to bilateral oophorectomy, with or without hysterectomy [5][6][7][8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations